IMPLEMENTATION OF MURABAHAH PRODUCT MARKETING STRATEGY OF SHARIA PUBLIC FINANCING BANK (BPR SHARIA) - Wawan Susanto; Novrida Qudsi Lutfillah; Soenarmi .; Yuyun Widiastuti (Department of Management - Faculty of Business and Economics. Universitas Surabaya., 2017)
This study aims to understand the implementation of marketing strategies for murabahah products in BPR Sharia in Lamongan. The research method used is a case study by interviewing the head and account officer of BPR Sharia Lamongan Branch as interviewees. The results showed that murabahah products in the implementation of marketing strategies applying a service marketing mix that has been adapted to the environment where BPR Sharia Lamongan Branch was located, including: (1) murabahah products that are sharia-based, (2) promotion using socialization strategies as well as sharia banking education programs, (3) an easy process, and (4) employees (human resources) who have honesty, trusteeship, and politeness, and can establish a family-like relationship with customers. The implementation of marketing strategies is interpreted as keeping trust entrusted to the welfare of the people.